2020
DOI: 10.3390/s20144049
|View full text |Cite
|
Sign up to set email alerts
|

Why Not Glycine Electrochemical Biosensors?

Abstract: Glycine monitoring is gaining importance as a biomarker in clinical analysis due to its involvement in multiple physiological functions, which results in glycine being one of the most analyzed biomolecules for diagnostics. This growing demand requires faster and more reliable, while affordable, analytical methods that can replace the current gold standard for glycine detection, which is based on sample extraction with subsequent use of liquid chromatography or fluorometric kits for its quantification in centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 90 publications
0
28
0
Order By: Relevance
“…To demonstrate the excellent and tuneable selectivity of our biosensor platform, we have used amino acids as target analytes as they present a high level of similarity and are known to be very difficult to discriminate between by established approaches. 11 Thus, the selectivity of our glycine and leucine sensing platforms was assessed against a panel of other common amino acids, including polar, non-polar, small, and bulky amino acids. An initial validation using optical (FRET) sensing showed that Cys-LeuFS was selective for leucine, with some weaker affinity for isoleucine and valine, while Cys-GlyFS was selective for glycine, with some weak affinity for leucine and valine (Fig.…”
Section: Cys-glyfsmentioning
confidence: 99%
See 4 more Smart Citations
“…To demonstrate the excellent and tuneable selectivity of our biosensor platform, we have used amino acids as target analytes as they present a high level of similarity and are known to be very difficult to discriminate between by established approaches. 11 Thus, the selectivity of our glycine and leucine sensing platforms was assessed against a panel of other common amino acids, including polar, non-polar, small, and bulky amino acids. An initial validation using optical (FRET) sensing showed that Cys-LeuFS was selective for leucine, with some weaker affinity for isoleucine and valine, while Cys-GlyFS was selective for glycine, with some weak affinity for leucine and valine (Fig.…”
Section: Cys-glyfsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Amongst established biomarker sensing techniques, which include fluorescence, enzyme-linked immunosorbent assays (ELISAs), and surface plasmon resonance, electrochemical approaches offer several desirable advantages such as miniaturization, low cost, and fast response times. [9][10][11] Electrochemical sensors are also capable of achieving very high sensitivity, with attomolar limits of detection having been attained by nanostructuring electrode surfaces using metal/metal oxide nanoparticles, carbon nanotubes, graphene, or conducting polymers. [12][13][14] Together, these characteristics have led to the widespread adoption of electrochemical sensing platforms in point-of-care (POC) and selfmonitoring applications such as blood glucose monitoring for diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations